Oropharyngeal teratoma: A case presentation and review of literature - Amina Lami Okhakhu; Ngozi Carol Onyeagwara (Wolters Kluwer Medknow Publications, 2022)
Teratomas are true neoplasms derived from the three germ layers. They are relatively rare tumours. They present in the sacrococcygeal region, gonads and retroperitoneum commonly. We present the report of a 5-month-old infant who presented with a prolapsing oropharyngeal teratoma and literature review.